Ensemble learning-based data-driven analytics for power system stability - Shu, Zhengge (Nanyang Technological University, 2023)
With the continuous development of society, electricity has become a necessity for human production and livelihood. In order to meet the increasing demand for electricity, modern power systems are developing towards ultra-high voltage, large capacity, and long-distance transmission. In addition, with the integration of a high proportion of renewable energy, the power grid structure has become increasingly complex. Studying the stability of the power system, extracting data on the stability situation of the power system through data-driven methods for analysis and stability analysis, is of great significance for improving the voltage stability of the power system and preventing large-scale power outages in the power system.